Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Liveworksheets terhadap Kemampuan Metakognitif dan Kemampuan Berpikir Kritis Siswa SMA di Kawasan Pertanian Industrial - Nurhaliza, Leny; Siswati, Bea Hana; Wahono, Bevo (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2024)
The metacognitive abilities and critical thinking abilities of high school students in Indonesia tend to be low. An appropriate learning model is needed to hone students' metacognitive and critical thinking skills. The learning model that can be applied is Problem Based Learning which is a problem-based learning model related to daily life and the surrounding environment. Problem-based learning can hone students' abilities in finding solutions to problems through the thinking process. This research aims to determine the effect of the Problem Based Learning learning model assisted by Liveworksheets on the metacognitive abilities and critical thinking abilities of high school students in industrial agricultural areas. This research was conducted using a quasi-experimental method at SMA Negeri 3 Jember with research subjects as class X students and data analysis using ANAKOVA. The research results show that the Problem Based Learning learning model assisted by Liveworksheets has an effect on metacognitive abilities with a significance level of 0.007 (Sig<0.05) and has an effect on students' critical thinking skills with a significance level of 0.000 (Sig<0.05).